Competency and Motivation Analysis on Educator Performance - Nurlina, Nurlina; Lestari, Neta Dian (Graduate Program Magister Manajemen Pendidikan, 2022)
The main educator in education is the teacher. Teachers as teachers in educational units or schools. Human Resources are individuals who work as drivers of an organization, both institutions, and companies, and function as assets that must be trained and their abilities developed. Human Resources is one of the resources contained in the organization, including all people who carry out activities. This study is to identify the performance of the quality of educators with the competence and motivation of teachers in the city of Palembang. The method used is descriptive, with a research sample of 150 elementary school teachers in the city of Palembang. The data collection used is observation, interviews, and documentation. The research results obtained are the performance of educators at various levels, namely medium, high, and very high. Teachers have good competence and motivation in their performance as educators. From this research, it can be concluded that teacher performance can be seen from their competence and motivation in the High category.